The Application of the Flipped Classroom Model Integrated with Google Classroom to the Student's Learning Motivation - Rizki Rahma Putri; Khairil Khairil; Safrida Safrida (Postgraduate, University of Mataram, 2022)
This study aims to determine the differences in students' learning motivation with the application of the flipped classroom combined with the google classroom with conventional methods on the concept of the human circulatory system at MAN 2 Banda Aceh. The method used is quasi-experimental, with a Pretest-Posttest design. The population in this study were all students of class XI IPA MAN 2 Banda Aceh, totaling 120 people. The sampling technique in this study was determined by theÂ purposive sampling technique. The instrument used in this study was a questionnaire. Data analysis used anÂ independent sample t-test. The results showed that there were differences in the application of the flipped classroom combined with the google classroom and the flipped classroom on the motivation for the concept of the human circulatory system at MAN 2 Banda Aceh. Conclusion: the application of the flipped classroom model combined with the google classroom is effective in increasing students' learning motivation compared to using conventional methods